Accurate determination of 3-alkyl-2-methoxypyrazines in wines by gas chromatography quadrupole time-of-flight tandem mass spectrometry following solid-phase extraction and dispersive liquid–liquid microextraction - Fontana, Ariel Ramón (2017)
A new reliable method for the determination 3-alkyl-2-methoxypyrazines (MPs) in wine samples based on the sequential combination of solid-phase extraction (SPE), dispersive liquid–liquid microextraction (DLLME) and gas chromatography (GC) quadrupole time-of-flight accurate tandem mass spectrometry (QTOF-MS/MS) is presented. Primary extraction of target analytes was carried out by using a reversed-phase Oasis HLB (200 mg) SPE cartridge combined with acetonitrile as elution solvent. Afterwards, the SPE extract was submitted to DLLME concentration using 0.06 mL carbon tetrachloride (CCl4) as extractant. Under final working conditions, sample concentration factors above 379 times and limits of quantification (LOQs) between 0.3 and 2.1 ng L−1 were achieved. Moreover, the overall extraction efficiency of the method was unaffected by the particular characteristics of each wine; thus, accurate results (relative recoveries from 84 to 108% for samples spiked at concentrations from 5 to 25 ng L−1) were obtained using matrix-matched standards, without using standard additions over every sample. Highly selective chromatographic records were achieved considering a mass window of 5 mDa, centered in the quantification product ion corresponding to each compound. Twelve commercial wines, elaborated with grapes from different varieties and geographical origins, were processed with the optimized method. The 2-isobutyl-3-methoxypyrazine (IBMP) was determined at levels above the LOQs of the method in half of the samples.